5x+11=-59-9x

Simple and best practice solution for 5x+11=-59-9x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+11=-59-9x equation:


Simplifying
5x + 11 = -59 + -9x

Reorder the terms:
11 + 5x = -59 + -9x

Solving
11 + 5x = -59 + -9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '9x' to each side of the equation.
11 + 5x + 9x = -59 + -9x + 9x

Combine like terms: 5x + 9x = 14x
11 + 14x = -59 + -9x + 9x

Combine like terms: -9x + 9x = 0
11 + 14x = -59 + 0
11 + 14x = -59

Add '-11' to each side of the equation.
11 + -11 + 14x = -59 + -11

Combine like terms: 11 + -11 = 0
0 + 14x = -59 + -11
14x = -59 + -11

Combine like terms: -59 + -11 = -70
14x = -70

Divide each side by '14'.
x = -5

Simplifying
x = -5

 

See similar equations:

| -65-9x=8x+20 | | 4x+1=2x+31 | | 6-(2z-8)=4-3z | | 7-7x=171-35x | | -8(1-5n)+7=-38+3n | | 60-6x=12x+16 | | 6(550-x)=5(550+x) | | 7a^2+40a+25=0 | | 16x^2-8x+82=0 | | 5n=20(4+.25n) | | 2x*x-4x-3=0 | | 42x^2-69x+20=7x^2-8 | | 7-4w=19 | | 7-(4x-4)=5-5x | | 8x-12=x | | 2x+10=82-6x | | 60-3x=10x+21 | | 4.8-9.6x=14.4 | | 3x+14=84-4x | | 80-4x=8x+20 | | 20x-3=30x+1 | | -54-2x=6-8x | | -71+n=-169 | | 159-5x=6x+5 | | 5x-3=30x+7 | | 4x+13=-47-18x | | 2x^2+5x-75=0 | | 2ax+3bx=0 | | 4x+13=-47-8x | | -77=x+(-41) | | 2yx+3zx=0 | | -4b=-4 | | 5a+4a= | | 3x+18=3x-16 | | 2(x-2)=-2(1-x) | | -5=-4k-k | | 7x-14-2x=9x-7 | | 2x+10=64-4x | | 6x+5x=0 | | 63-5x=8x+24 | | -.25x+6=.6x+28 | | x^2+12b-64=0 | | -16+2x=4x-(16+12) | | -29-3x=7-9x | | 5+2n-6n=1 | | 116-2x=5x+18 | | x^2+12x-64=0 | | 2x+10=-26-10x | | 9w+72=7+8w | | -69-7x=8x+21 | | 8-(4n-2)=8-5n | | 14-9x=46-37x | | x^4-12x^3+36x^2=0 | | 3x-42=-3(x+4) | | 227-2x=43x+17 | | m+(-96)=-55 | | 9x-30=60 | | 6y-2=-15+y | | 2(x-2)+16=5x-9 | | 4(x+9)+2=38 | | 4(2x-4)=7x+2 | | 8x+8=6x+16 | | 4x-8+3x+27=28 | | -12=-6a-6a | | 6x+84=12x+12 |